2007
DOI: 10.1002/ppap.200600218
|View full text |Cite
|
Sign up to set email alerts
|

Porous SiOCH, SiCH and SiO2 Etching in High Density Fluorocarbon Plasma with a Pulsed Bias

Abstract: The effect of radio frequency bias pulsing on porous SiOCH, SiCH and SiO2 etching using inductively coupled fluorocarbon plasmas was investigated. It was found that pulse frequency had only a small influence on material etch rates. However, pulse duty cycle, defined as the time during which a bias is applied over the total period, clearly modified etch rates and selectivities. Indeed, etch selectivities between porous SiOCH and SiCH or SiO2 were considerably improved when the duty cycle was decreased. This enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…It was concluded that pulsing the RF bias did not offer any selectivity advantages compared to CW plasma. Raballand et al [120] studied etching of SiOCH (a low-k dielectric), SiCH (an etch stop layer) and SiO 2 (a masking layer) in CHF 3 ICP with pulsed bias (1500 W source power, 40 sccm flow and 5 mTorr pressure). In accordance with Schaepkens et al [119], they observed that the etching rate of porous SiOCH was independent of PRF, in the range 1 Hz to 10 kHz investigated, but depended on duty ratio.…”
Section: Etching Of Si-based Materialsmentioning
confidence: 99%
“…It was concluded that pulsing the RF bias did not offer any selectivity advantages compared to CW plasma. Raballand et al [120] studied etching of SiOCH (a low-k dielectric), SiCH (an etch stop layer) and SiO 2 (a masking layer) in CHF 3 ICP with pulsed bias (1500 W source power, 40 sccm flow and 5 mTorr pressure). In accordance with Schaepkens et al [119], they observed that the etching rate of porous SiOCH was independent of PRF, in the range 1 Hz to 10 kHz investigated, but depended on duty ratio.…”
Section: Etching Of Si-based Materialsmentioning
confidence: 99%
“…Plasmas of perfluorocyclobutane (c-C 4 F 8 , symbolized hereafter as C 4 F 8 ) and mixtures of C 4 F 8 with Ar, O 2 and H 2 have been widely used in the area of dielectric etching in microelectronics fabrication. In particular, they have been used for the etching of SiO 2 [1][2][3] and have been tested [4][5][6] for the etching of low-k and porous materials together with other fluorocarbon (fc) gases, such as CF 4 , CHF 3 and C 2 F 6 [7,8]. C 4 F 8 has been also used for plasma enhanced chemical vapour deposition of fc films [9][10][11], which are exploited either as low-k films or in bio-fluidic applications [12].…”
Section: Introductionmentioning
confidence: 99%
“…The guard ring avoids edge effects and maintains a flat sheath above the disc. Figure 7 shows the biasing of the probe [17]. The disc and guard ring are biased at −60 V in order to repulse all electrons.…”
Section: Methodsmentioning
confidence: 99%